Urban 'beautification' and its discontents: the erosion of urban commons in Milan. Issue 4 (3rd April 2022) - Tartari, Maria; Pedrini, Sabrina; Sacco, Pier Luigi
ABSTRACT : In this paper, we analyze the relationship between artistic interventions in the public space and their impact on urban cultural commons. We focus on the case study of the Muri Liberi street art project in NoLo, a semi-peripheral neighbourhood of Milan traditionally characterized by a multi-ethnic, low-income resident population and now witnessing the early signs of socio-economic transformation. We propose a comparison with a case of art-based regeneration in another semi-peripheral neighbourhood of Milan, the Ortica district, specifically the Or.Me project. We study how the analyzed street art projects functioned, in the NoLo case, as a symbolic appropriation of the public space of the neighbourhood that bypassed its longtime residents and undermined their local urban commons, as a likely premise to future gentrification of the neighbourhood; in the Ortica case, we show instead how a community-based public art project in a similar context can foster social cohesion and improve a functional relation between the local community and its commons. We comment on how disregarding the political implications of artistic 'beautification' projects negatively impacts the social sustainability of art-driven urban renewal projects and delegitimizes the social credibility of public art as an anti-hegemonic practice.